2010
DOI: 10.1088/0953-4075/43/14/144019
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen emission location, temperature and inward velocity in the peripheral helical plasma as observed with plasma polarization spectroscopy

Abstract: The behaviour of neutral particles around the ergodic layer has been investigated by H α spectral profile measurements by means of a polarization-separation technique. Emission locations, atomic temperatures and velocity components along the lines of sight at the inner and outer peripheral regions are determined for a large helical device plasma with a magnetic field axis of R ax = 3.80 m. A high intensity of H α emissions is localized around the ergodic layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Once the U CX is obtained, the spatial and velocity distribution of the hot atoms n H hot (R, v) is calculated with the same form to Eqs. (A1) and (8).…”
Section: Appendix: Transport Calculation Of Hot Atoms Including Multimentioning
confidence: 97%
See 2 more Smart Citations
“…Once the U CX is obtained, the spatial and velocity distribution of the hot atoms n H hot (R, v) is calculated with the same form to Eqs. (A1) and (8).…”
Section: Appendix: Transport Calculation Of Hot Atoms Including Multimentioning
confidence: 97%
“…6 Iwamae et al combines a polarization-resolved spectroscopic technique with the Zeeman split analysis method for increasing the measurement accuracies. 7,8 They have measured the Balmer-a line shape for large helical device (LHD) with eight LOSs with their polarization resolved. They determined the emission locations of the Balmer-a line from the polarization dependence of the line shapes by the Zeeman split.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multiple LOSs measurement with this technique has been performed by Shikama et al [8]. Iwamae et al have demonstrated the emission location measurement of the hydrogen atoms for the Large Helical Device (LHD) with an aid of the polarization-resolved spectroscopic technique [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular and atomic hydrogen is ionized mainly in peripheral regions of magnetic fusion plasma, so their ionization flux is highest along plasma edges. [1][2][3] Nevertheless, through charge exchange collisions with hot protons, some fraction of the atoms penetrates deep inside the plasma as neutral hydrogen and acts as a source of electrons and protons in the core region. [4][5][6] We recently investigated detailed line profiles of Balmer series emissions from high temperature plasmas generated in the Large Helical Device (LHD) 7 and found that emissions from high temperature atoms in the core region of the plasma appear in the far wing portions of the profile, while those from the peripheral region appear in the central part.…”
Section: Introductionmentioning
confidence: 99%